Peran Kepercayaan Pelanggan Dalam Memediasi Pengaruh E-WoM Terhadap Keputusan Pembelian Electronic Di Shopee - Wadiyastuti, Septiana; Suherman, Enjang; Khalida, Laras Ratu (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to examine the influence of e-wom (electronic word of mouth) and customer trust on the purchase decision of electronic goods products on Shopee, as well as to find out whether customer trust mediates the relationship between E-wom and purchase decisions. This study also aims to provide a better understanding of the factors that influence consumer purchasing decisions, especially in the context of purchasing electronic goods at Shopee among students. This study used a verifiative descriptive research method with a quantitative approach. The sample used was 96 people who used a random sampling technique that used a direct random selection technique for Shopee users. This analysis uses the path analysis method. The results showed that (electronic word of mouth) E-wom had a positive and significant effect on customer trust, but did not have a positive and significant effect on purchasing decisions. Customer trust also has a positive and significant effect on purchasing decisions. The E-wom variable has an indirect influence on purchasing decisions through customer trust as a mediation variable. Therefore, it is important to pay attention to the role of customer trust in influencing purchasing decisions, especially in the context of technology transactions.